CARA BELAJAR WARGA BELAJAR PAKET C DI PKBM MITRA RIAU JAYA CEMERLANG PEKANBARU - Frengki Sitanggang Sitanggang; Titi Maemunaty Maemunaty; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The formulation of the problem in this research whether the learning style of students group C at PKBM Mitra Riau Jaya Cemerlang Pekanbaru is classified good level. And the objective of this research in order to know about learning style of students group C at PKBM Mitra Riau Jaya Cemerlang Pekanbaru. This is descriptive research by quantitative approach. In addition, the researcher chose thirty people as the samples of this research that was taken from fifty people as the population of this research. The researcher took the samples by using random sampling. In collecting data, the researcher used questionnaire as the research instrument which contains forty statements. Furthermore, the alternative answer of each statement has four categories which always category is given score 4, an often category is scored 3, sometimes categories is scored 2, and never categories is scored 1. Based on the research findings, learning style of students group C at PKBM Mitra Riau Jaya Cemerlang Pekanbaru is excellent. It was proven from the description of data recapitulation as the follows: 1) in the ways of making schedules, there are 91,2 % respondents determined always and often, 2) in the ways of reading, there is 89,6% respondents determined always and often, 3) in the ways of reviewing the material, there are 85,7% respondents stated always and often, 4) in the ways of concentrating, there are 91,4% stated always and often, 5) in the ways of doing tasks, there are 89,8 % stated always and often. Therefore, the researcher concluded that the learning style of students group C is classified excellent. Keywords: Learning Style, Students, Group C